An Overview of Traditional Medicinal Plants Used in Treating Hepatocellular Carcinoma (HCC) with Emphasis on Mechanisms of Action: Traditional Medicinal Treatment of Hepatocellular Carcinoma (HCC) - Adekilekun, Habeebulahi Ajibola; Oyewusi, Habeebat A.; Odoma, Saidi; Kirimuhuzya, Claude (Journal of Tropical Life Science, 2024)
Cancer is an incurable fatal disease wreaking havoc on the population of countries either developed or developing. Hepatocellular carcinoma (HCC) is the fifth most frequent type of cancer having a poor prognosis. Globally, HCC management and treatment intervention using medicinal plants from generation to generation is rapidly increasing and remains an area of promising research. This review provided insight into medicinal plants' ethnomedicinal use, photochemistry and mechanisms of action on HCC exhibiting anti-cancer potentials subjected to scientific investigations. Furthermore, clinical, toxicity studies and detailed mechanisms of action would provide an understanding of the development of lead compounds in drug discovery and development for HCC